2007
DOI: 10.1007/s10549-007-9602-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combined aerobic and resistance exercise program in breast cancer survivors: a randomized controlled trial

Abstract: Few randomized controlled trials have examined the effects of combined aerobic and resistance training in breast cancer survivors soon after completing adjuvant therapy. Breast cancer survivors (N=58) within 2 years of completing adjuvant therapy were randomly assigned to an immediate exercise group (IEG; n=29) or a delayed exercise group (DEG; n=29). The IEG completed 12 weeks of supervised aerobic and resistance exercise, three times per week. The DEG completed the program during the next 12 weeks. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
188
1
22

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(221 citation statements)
references
References 24 publications
10
188
1
22
Order By: Relevance
“…Se localizaron 8.557 títulos, de los cuales tras la aplicación de los criterios de selección definidos, sólo 11 estudios (n = 1.407) fueron incluidos en el presente estudio 24,25,26,27,28,29,30,31,32,33,34 . La Figura 1 presenta el diagrama de flujo con los procesos de búsqueda y selección de los estudios incluidos.…”
Section: Resultados Características De Los Estudios Incluidosunclassified
See 2 more Smart Citations
“…Se localizaron 8.557 títulos, de los cuales tras la aplicación de los criterios de selección definidos, sólo 11 estudios (n = 1.407) fueron incluidos en el presente estudio 24,25,26,27,28,29,30,31,32,33,34 . La Figura 1 presenta el diagrama de flujo con los procesos de búsqueda y selección de los estudios incluidos.…”
Section: Resultados Características De Los Estudios Incluidosunclassified
“…Solo tres estudios reportaron el seguimiento realizado en sus metodologías 26,30,31 . Courneya et al 26 encontraron que las diferencias en la fatiga, el funcionamiento físico y la calidad de vida no fueron significativas a los 6 meses de seguimiento post-intervención (p = 0,054).…”
Section: Resultados Características De Los Estudios Incluidosunclassified
See 1 more Smart Citation
“…Three other studies [4,11,22] reported long-term results following an exercise intervention for cancer patients who had completed their cancer-related treatment. Similar to our findings in a mixed group of cancer survivors, Milne et al [22] showed that quality of life of breast cancer survivors was improved directly after and 3 months following a 12-week combined aerobic and resistance exercise intervention. Contrary to the findings in the present trial, they reported that quality of life still increased from post-intervention to 3-month post-intervention.…”
Section: Change (Points)mentioning
confidence: 99%
“…The majority of physical intervention studies with breast cancer survivors have been conducted following the completion of cancer treatment. In general the research has shown that post-treatment physical activity programmes can have positive effects on a wide range of outcomes (Cramp & Daniel, 2008) including quality of life (Carson et al, 2009;Daley et al, 2007), physical functioning Pinto et al, 2005), aerobic capacity (Burnham & Wilcox, 2002;Milne et al, 2008), and mental wellbeing (Cho et al, 2006;Morey et al, 2009). A recent meta-analysis also found positive effects of physical activity on a wide range of QOL outcomes across different cancer-site survivors, although it should be recognised that 65% of the reviewed studies included breast cancer patients only (Fong et al, 2012).…”
Section: Length Of Interventionmentioning
confidence: 99%